Structure of starch hydrolysates following in vitro oral digestion: Effect of botanical source of starch and hydrothermal treatments. Issue 9 (18th February 2013) - Nantanga, Komeine K. M.; Bertoft, Eric; Seetharaman, Koushik
Abstract Digestion of starch in humans occurs progressively in the gut. However, the literature is scant on the structures of the starch digestion products along the gut from the mouth to the small intestines – products that impact glucose homeostasis. This submission focuses on the first step of starch digestion, i.e., impact of human salivary amylase on the structure of hydrolysis products obtained from cooked starches from different botanical sources. Normal corn (NCS), normal wheat (NWS), and normal potato (NPS) starches were cooked at 1:0.7 (T0.7) or 1:2 (T2) starch:water ratios. Cooked starches were subjected to salivary amylase at conditions mimicking oral digestion. Extent of hydrolysis was lower at T0.7 compared to T2, but the amount of carbohydrates in different fractions and the MW profiles within each treatment showed no apparent differences between starches from different botanical sources. However, debranching of the hydrolysates revealed structural differences between the different starches with regards to extent of amylose hydrolysis and the amount and profile of lower MW fractions. Therefore, the structures of hydrolysates that are likely the substrate for subsequent hydrolysis in the gut are different based on cooking condition or botanical source of starch, with potential consequence for glucose homeostasis.